A Short Version of the Pain Anxiety Symptoms Scale (PASS-20): Preliminary Development and Validity - Lance M McCracken; Lara Dhingra (Pain Research and Management)
BACKGROUND: Research has shown significant relations between fear and avoidance of pain and the suffering and disability of chronic pain. Effective measurement tools have formed the foundation for studying these relations.